Clube de Cinema de Fortaleza: sociabilidade intelectual e cultura cinematográfica na cidade de Fortaleza (1948-1963) - Pereira, Raul Kennedy Gondim (2017)
The present work is dedicated to the comprehension of the experience of the Film Club of Fortaleza (FCF), between its foundation in 1948 and the middles of the 1960's, when there were important changes in the institution and in the film club movement in Brazil. This research is about the intellectual sociability and the film club culture of the FCF through exhibitions, debates, lectures and writing about cinema. Our focus is on the area around the comercial center of Fortaleza (Centro), since its history is related to many institutions of this city, such as the regular journals (Unitário, Correio do Ceará, Gazeta de Notícias and O Povo) – specially in the writings about cinema and film clubs by Antônio Girão Barroso. We have studied the history of the FCF and its members from the perspective of wide net of intellectual sociability related to other institutions such as the English course IBEU (Instituto Brasil-Estados Unidos), the printing association Associação Cearense de Imprensa (ACI), bookshops, the university Universidade Federal do Ceará (UFC), among others. The methodological approach about the history of film clubs, according to Baecque (2010), is drawn upon different sources such as: personal files, documents of the FCF kept at Casa Amarela da UFC – programs, bulletins, infos and the mailing files – as well as journal files and memory books.